FORMULASI DAN EVALUASI FISIK SEDIAAN MASKER CLAY KOMBINASI EKTRAK ETANOL DAUN BAWANG DAYAK DAN KULIT JERUK SIAM - Musiam, Siska; Ma'ruf, Muhammad; Kumalasari, Eka (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Clay masks are a popular cosmetic due to their ability to rejuvenate the skin and detoxify the face. Clay masks can be made by adding dayak onion leaves and Siamese banjar orange peel, known to be rich in natural antioxidants containing various complex secondary metabolites. The aim of this research is to formulate and evaluate a clay mask preparation made from a combination of ethanol extracts of dayak onion leaves and Siamese banjar orange peel. The samples were extracted using the maceration method with 70% ethanol as a solvent. The ethanol extracts were then formulated into clay masks using kaolin as the base material, with ratios of 1:1, 2:1, and 1:2. The organoleptic evaluation showed no changes in color, odor, or texture of the masks during storage. All formulations were homogeneous with an average pH ranging from 5.19 to 5.97. The viscosity test results ranged from 29.14 to 37.05 Pa’s, the average spreadability was 27.12-38.90 mm, and the drying time ranged from 15.21 to 17.58 minutes. It can be concluded that the ethanol extract combination of dayak onion leaves and Siamese banjar orange peel can be formulated into a stable clay mask and all formulations meet the required physical evaluation.